Paradox Artificial Intelligence: Encourage Innovation or Kill Thoughts? - Wirawan, Abdul Karim; Saputri, Vina Amalia (Proceeding International Conference on Education, 2024)
Artificial intelligence (AI) has brought about major innovations in various fields, from technology to education. However, behind these advances, there are concerns about the impact of AI on human thinking abilities. This article examines the dilemma humans face in adopting AI, likened to a paradox—between beneficial innovation and the potential destruction of critical thinking. To discuss this topic, this article focuses on two discussions. First, how society and individuals can balance the benefits of AI innovation with the risks of weakening critical thinking abilities and autonomy of thinking? Second, whether ethical boundaries need to be applied in the use of AI to avoid negative impacts on human intellectual abilities. By combining theoretical reviews and case analysis, this article highlights how AI can optimize productivity and innovation while questioning whether excessive dependence on technology can hinder humans' ability to think independently and critically. The discussion also touches on ethical aspects, where considerations need to be made in setting limits on the use of AI so as not to threaten human cognitive abilities and creativity. Ultimately, this article aims to provide a deeper understanding of how AI can be a tool for innovation as well as a potential threat to human intellectual development.